Administrative and organizational capacities of civil society in EU Cohesion Policy - Potluka, O.; Medeiros, E. (Regional Studies, 2024)
Administrative capacities are among the crucial factors influencing success in European Union (EU) Cohesion Policy absorption. The current research concentrates on the public sector, while administrative capacities in other stakeholders are omitted. Our research focuses on whether local stakeholders from civil society have sufficient capacities to contribute effectively and efficiently to EU Cohesion Policy implementation. We performed our research on 57 integrated urban development plans in Czechia and Portugal and conducted 33 interviews with local entities. The results indicate a different level of capacity not only between the public and civil society organizations but also within civil society.